Effect of Different Ranges of Selection Intensity to Compare the Expected Response According to Different Selection Methods in Saanen Goats - Arfan A. Meeto; Zaid M. M. Al-Azzawi (Genius Journals, 2023)
The study was conducted at the private Rasan Agricultural Station for the breeding of Saanen goats in Halabja Governorate, located east of Sulaymaniyah Governorate in the Kurdistan Region of Iraq. The research included 268 records belonging to 74 does from the station's records for the seasons 2021 and 2022. The station was established in 2020 by importing 500 heads of the Saanen goats from the Netherlands, with the aim of estimating the direct genetic gain and the response associated with selection at different ranges of selection intensity (70 and 50%) and comparing them according to Different selection methods depending on the phenotypic values of total milk yield, birth weight and the economic value resulting from them, as well as the total milk yield and preweaning average daily gain and the economic value calculated from them. The direct genetic gain ratios for does and bucks were 3.79, 5.83 and 4.75, 6.68%, depending on total milk yield, 2.86, 4.71 and 3.48, 5.34% depending on birth weight, 3.65, 5.69 and 4.61, 6.54% depending on economic value calculated from them at a selection rate of 70 and 50%, respectively. The direct genetic gain ratios for does and bucks were 3.44, 5.44 and 3.68, 6.43% depending on the pre-weaning average daily gain 0.41, 1.1 8 and 0.97, 1.80% depending on Total milk yield and pre-weaning average daily gain at a selection rate of 70 and 50%, respectively, The values of family selection efficiency for total milk yield, birth weight and pre-weaning average daily gain were 0.204, 0.190 and 0.201, respectively. The study showed the superiority of bucks over does by the direct genetic gain and the response associated with selection, the resultant depending on the phenotypic value of the characteristic of total milk yield, birth weight and the economic value resulting from them, as well as the phenotypic value of the characteristic of total milk yield, the pre-weaning average daily gain and the economic value resulting from them, in addition to that individual selection (does) is better of familial selection (bucks) in this study
Keywords: pre-weaning; characteristic; daily gain; economic